Development of Student Magnetic Inquiry Project Results Sheet (SMIPRS) Integrated with Local Wisdom and Islamic Values - Kurniawan Arizona; Joni Rokhmat; Agus Ramdani; Gunawan Gunawan; AA Sukarso (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2023)
This study includes research and development of the integrated Student Magnetic Inquiry Project Results Sheet (SMIPRS) of Local Wisdom and Islamic Values using the ADDIE development model, which aims to: 1) Describe SMIPRS integrated local wisdom and Islamic values, 2) Describe student responses to SMIPRS integrated with wisdom local wisdom and Islamic values, 3) describe the effectiveness of using SMIPRS integrated with local wisdom and Islamic values. The test subjects in this study were 33 students. SMIPRS trials in this study by providing SMIPRS and student response questionnaires and tests related to magnetism material. The study offers expert validation test results with very suitable criteria (95.83%). Meanwhile, student responses to implementing the SMIPRS integrated with local wisdom and Islamic values agreed (87.9%) to be implemented. Based on the effectiveness test, SMIPRS had a significant effect after it was implemented by students in the learning process (sig. = 0.000) with an average pretest and post-test difference of 23.61.